Pediatric Autoimmune Hepatitis - Silvia Nastasio; Marco Sciveres; Paola Francalanci; Giuseppe Maggiore (MDPI AG, 2024)
Pediatric autoimmune hepatitis (PAIH) is a rare necro-inflammatory disease of the liver of unknown etiology thought to derive from the dysregulation of the immune response upon exposure to environmental triggers in genetically predisposed individuals [...]